Livestock, livestock loss and livelihood: a note on Mishing char dwellers of Assam - Saikia, Mrinal; Mahanta, Ratul (Society Register, 2023)
The geography of char (the sandy land areas found within the river or lining at the bank) and their fertile lands create a suitable environment for livestock rearing, significantly contributing to livelihood, income, and nutritional intact for the char dwellers. The study investigates how livestock rearing and losses due to diseases and disasters are related to the livelihood and economy of the char-residing people, with a particular concentration on the Mishing char dwellers of Assam. The study considers two districts of Assam having char areas populated by the Mishing population. Both quantitative and qualitative tools are used to achieve the desired goals. Table and box plot figures are used to present the results. It is found that the loss of livestock is a serious threat to the economy of char dwellers. It contributes the most significant portion of their economic loss. It is also found that the severity is higher in case of disease loss of livestock than disaster loss. The study further suggests possible adaptation strategies for reducing livestock loss in the study area.